2017
DOI: 10.1093/eurpub/ckx213
|View full text |Cite
|
Sign up to set email alerts
|

A nationwide serosurvey of hepatitis E virus antibodies in the general population of Portugal

Abstract: The present nation-wide survey provides insight in the epidemiology of HEV in Portugal and confirms that HEV is endemic in the Portuguese population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 22 publications
3
19
5
Order By: Relevance
“…The association of HEV seropositivity with age observed in our study has also been reported by others [7][8][9][10][11][12][13][14][15][16][17][18][19][20] and may be explained not only by the cumulative lifetime exposure to HEV, but also by cohort effect, where certain population groups were more likely to be exposed to the virus during their life.…”
Section: Epidemiology and Infectionsupporting
confidence: 90%
See 1 more Smart Citation
“…The association of HEV seropositivity with age observed in our study has also been reported by others [7][8][9][10][11][12][13][14][15][16][17][18][19][20] and may be explained not only by the cumulative lifetime exposure to HEV, but also by cohort effect, where certain population groups were more likely to be exposed to the virus during their life.…”
Section: Epidemiology and Infectionsupporting
confidence: 90%
“…Human HEV infection, investigated using seroprevalence studies, was found to be more prevalent in older ages [7][8][9][10][11][12][13][14][15][16][17][18][19][20], lower socio-economic status [21], poorer residence areas [9,[14][15], among sheltered homeless adults [22] or uneducated people [14], specific nationalities (for example, higher in mixed race donors and ethnic groups within China [12,15], or in immigrants from Afghanistan [14]), drinking water from wells or rivers [15], consumption of meat products [7,15,17,23] especially pork [24,25] and following blood transfusions [1].…”
Section: Introductionmentioning
confidence: 99%
“…Several countries worldwide have reported the detection of HEV in wastewater samples [8,9,10]. Since Portugal is considered an endemic country for HEV [11,12] and past studies have confirmed the presence of HEV in swine [2,13], it is expected that HEV could be released into the aquatic environment. To the best of our knowledge, no study on the detection of HEV or any viral enteric pathogen in wastewater has ever been carried out in Portugal.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, even seroprevalences in Europe are very difficult to compare in consequence of these serology limitations and very different rates have been reported across the continent, ranging from 1.3 to 52% [44][45][46]. In Finland, anti-HEV IgG seroprevalence was found to be 27.6% in general population [47], while in Norway, Germany and Portugal reported seroprevalences were 11.4%, 16.8% and 16.3%, respectively [48][49][50]. Furthermore, several countries such as Netherlands, Spain, France, and Southwest England have performed these studies in healthy blood donors reporting an anti-HEV IgG prevalence ranging from 16.0 to 26.7% [51][52][53][54].…”
Section: Discussionmentioning
confidence: 99%